Pengembangan Media Ular Tangga Bilangan Bulat pada Pelajaran Matematika di Sekolah Dasar - Defa Defa (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This study aims to determine the feasibility and effectiveness of the Integer Snakes and Ladders media in mathematics lessons on integer calculation material in grade VI elementary school. The subjects of this study were students of class VI Elementary School 11 Rantau Selatan totaling 30 people. This research uses Research and Development (R&D) research. Data validation was carried out by material experts and media experts, as well as by comparing student learning outcomes before and after using Integers Snakes and Ladders Media. The value of the media expert validation results at stage 1 was 70% with the